The Implementation of Among-Asuh Method in Guidance and Mentoring Management to Shape the Cadetsâ€™ Noble Character (a Case Study in the Military Academy) - Royke Deksino, George; Florentinus, Totok Sumaryanto; Fakhruddin, Fakhruddin (Universitas Negeri Semarang, 2017)
The education system in the Military Academy applies a basic education coursework including the formation of attitudes and behaviors, knowledge and skills, as well as physical skills through the process of teaching, training, and caring. However, in the process of organizing education, it is found that a Military Academy Cadet (Taruna) still conducts behavioral deviations. This is an indication of the weaknesses of the guidance and mentoring management done by the Cadets Regiment in shaping the character of the Cadets using the method of â€œAmong Asuhâ€. This study aims to describe and analyze the functions in the guidance and caring management of the Cadets; it also intends to find a model of guidance and caring management using â€œAsah-Asuhâ€ methods to shape the noble characters of the Cadets. This case study used a qualitative approach in line with Yin's theory on a single dimension. Data sources from informants of the staff of the caregivers of the Cadets Regiment, and the Military Academy and the documents. Data analysis techniques with triangulation techniques include tools, sources and social context i.e. data collection, data reduction, display data and verification/conclusions. The findings of the study are the weakness of the planning function which has not been accompanied by a thorough needs analysis of the caregivers of the Cadets Regiment, and there is no standard of caregiver competence in the Military Academy Cadets Regiment.